Planejamento de cadeias globais farmacêuticas incorporando análise financeira - Arruda, Pierre Martines de (2021)
In the last decades, the pharmaceutical industry has been going through an internationalization process of its operations. Due to the coronavirus disease (COVID-19), the planning of global pharmaceutical companies was directly affected in the search for an immunizing agent. In this context, the complexity of the supply chain increases, as economic and financial aspects influence the planning of the physical configuration of these networks. To date, the literature on optimization models for global supply chains, specifically for pharmaceutical production, does not incorporate financial feasibility issues in planning. In this way, this dissertation proposes to develop an optimization model for the global supply chain planning problem of a pharmaceutical industry incorporating financial indicators, mainly of investment viability. The model incorporates: (i) the net present value (NPV) in the objective function; (ii) the possibility of using equity or raising funds through loans and financing to open plants and distribution centers; (iii) the incorporation of compound interest in the calculation of financial expenses and; (iv) the alternative of investing the company's equity in the financial market. The problem addressed involves strategic decisions such as number, and location of secondary plants and distribution centers to meet the demand of the final markets, as well as the flow of products in the network. The model is tested with data based on two pharmaceutical companies with global operations that are producing vaccines for the Sars-CoV-2 virus. The results generated by the model were adequate, the following characteristics: the production of vaccines presented positive NPV, the financial analysis shows the high return on investments, and the opening of distribution centers (DCs) were outsourced. The contribution of this work is the incorporation of little-used financial aspects in global supply chain planning problems, allowing managers to make a better strategic decision based on the interconnection between operational management and corporate finance.